Գիտության հայազգի երախտավորը. Ֆրիդրիխ Կառլ Անդրեաս - Տիգրան Սարուխանյան (ՀՀ ԳԱԱ հրատ.)
Имя одного из выдающихся востоковедов – Фридриха Карла Андреаса (Багратяна, 1846–1930), хорошо известно многим поколениям ученых, специалистам по Ближнему и Дальнему Востоку. Андреас стал первым ученым, прочитавшим манихейские фрагменты из Турфана. На основании этих текстов Андреас определил средние иранские языки и их диалекты, однако ученый не ограничивался только исследованиями по Ирану. Существует достаточно много неопубликованных и неизученных рукописей, текстов и писем, которые до сих пор хранятся в библиотеке Геттингенского университета, ставшего хранителем архивов своих выдающихся ученых. The name of one of the prominent orientalists – Friedrich Carl Andreas (Bagratyan, 1846–1930) – is well known to many generations of scholars specialized in the studies on the Middle and Far East. Andreas’ main contribution to the scholarship was, that he was the first person to read the Manichean fragments taken from Turfan, based on which he identified the Middle Iranian languages and dialects. Andreas did not limit himself with the studies on Iran. Less has been written about the unpublished and unstudied manuscripts, handwritings and letters that are still kept at the Library of the University of Göttingen, which has become the depository of its large estates.
Keywords: History; Biography; Auxiliary Sciences of History; Philology; Linguistics; Language and Literature; D History